Teaching Speaking of Hotel Room Service Information by Using Comic Strip via Google Meet Application - Putu Ngurah Rusmawan; Ely Trianasari; Ninik Sri Rahayu Wilujeng (Universitas Pendidikan Mandalika, 2021)
During Covid 19 teaching and learning should be conducted via an online system. One of the supporting tools is using the application of google meet. The student in the tourism business management department must able to speak English in descriptive text fluently. The students must be provided excellent English skills to escort and to explain the clear hotel room facilities and services for international guests. The comic strip is teaching media that is suitable in-state polytechnic of Banyuwangi because it can help the student to understand the text easily. The lecturer tried to describe the teaching speaking activity in the classroom using the google meet platform. The study used a descriptive qualitative research design. The researcher analyzed and described the teaching speaking in the descriptive text by using comic strip for the tourism department. The preparation of the lecturer was syllabus and course agreement which consist of learning objective and indicator, the method, and learning sources. The lecturer taught the students based on course agreement. The lecturer only facilitated the students to be active in speaking descriptive text. He asked the students to do modeling communication in a hotel. One of the students performed as a bell boy and the other as a tourist who wants to stay in a hotel. During the teaching-learning process, the lecturer got three main troubles in conducting the teaching process. There was students’ low in vocabulary, pronunciation, losing signal, and trouble in expressing sentences. Speaking descriptive text course which was taught by the lecturer proceeded effectively and acceptable for the students.